Ритмы «умной толпы»: танцевальный флешмоб как явление современной массовой культуры - Дункевич, С.Г. (Культура народов Причерноморья, 2014)
В статье охарактеризован танцевальный флешмоб как относительно новое, но очень
популярное явление современной массовой культуры. На основе теоретического и практического
материала проанализированы условия возникновения, принципы организации, отличительные
особенности танцевальных флешмобов в мировой и отечественной практике. У статті охарактеризовано танцювальний флешмоб як відносно нове, але дуже популярне
явище сучасної масової культури. На основі теоретичного і практичного матеріалу проаналізовано
умови виникнення, принципи організації, характерні особливості танцювальних флешмобів у світовій та
вітчизняній практиці. In the article dancing flash mob is described as relatively new but very popular phenomenon of
modern mass culture. On the basis of theoretical and practical materials the terms of origin, principles of
organization, distinctive features of dancing flash mob in the world and domestic practice are analysed.
The author exposes genetic connections of flash mob with other demonstrations of actionism, such as a carnival
culture, performance and happening. In the article it is proved that on the modern stage of dancing flash mobs
are the brightest, the most spectacular and memorable flashmob-actions, which provide the heightened interest
to them from the audience of electronic tools of communication (first and foremost visitors of the popular
internet site «YouTube»). Modern flash mob is addressed just to the virtual instead of real audience that compels
to get involved professional producers, choreographers, dancers, video statements to its organization and
conducting. For the same reason political, economic and social factors exerts the large influence on frequency
of conducting of dancing flash mobs and their scenarios but it conflicts with ideology of organizers of the first
flash mobs. It is convincingly proved, that modern dancing flash mob frequently only imitates such canonical
features of the given type of activity as creativity, spontaneity, and absence of single center is guidance, absence
of commercial benefit and political personal interest. This fact is confirmed, for example, by organization of
flashmob-festivals or appearing of professional organizers of flashmob-actions which regarding their
conducting as a type of business.